CHARACTERISTICS AND POTENTIAL OF VETIVER GRASS (Chrysopogon zizanoides) TO SLOPES REINFORCEMENT AND EROSION MITIGATION - Hanggari Sittadewi (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Plant roots have the function of reducing groundwater that is saturated by rainwater, strengthening soil aggregation so that it supports plant growth and prevents erosion, increases infiltration, and holding capacity. Vertical soil stabilization is also carried out by the plant root system and also the effect of drainage that occurs through the process of water absorption and transpiration. This indicates that root system of plants has an important contribution to slope reinforcement and erosion mitigation. Vetiver grass (Chrysopogon zizanioides) is an perennial grasses that has been shown to slope reinforcement and erosion mitigation, because vertiver grass has physical, mechanical and hydraulic characteristics that support the stabilization mechanism. The unique root system is the fibrous root with fine and massive structure, fast growing and deep, has an average tensile strength of 75 MPa provides a stability effect. Dense hedgerows of vetiver grass with rigid stems formed from rows of plants can fuction as structure of a highly effective water transfer for spreading and diverting to stable areas so that the possibility of erosion is controlled. This paper presents the results of a study on the ability of vetiver grass to strengthen slopes and erosion mitigation by exploring the physical, mechanical and hydraulic characteristics of the plant. Keywords : vetiver grass, physical, mechanical and hydraulic characteristics, slopes reinforcement, erosion mitigation.